Entropy Generation Analysis and Performance Comparison of a Solid Oxide Fuel Cell with an Embedded Porous Pipe Inside of a Mono-Block-Layer-Build Geometry and a Planar Geometry with Trapezoidal Baffles - J. J. Ramírez-Minguela; J. M. Mendoza-Miranda; V. Pérez-García; J. L. Rodríguez-Muñoz; Z. Gamiño-Arroyo; J. A. Alfaro-Ayala; S. Alonso-Romero; T. Pérez-Segura (Entropy)
An analysis of entropy generation and a performance comparison are carried out for a solid oxide fuel cell with an embedded porous pipe in the air supply channel of a mono-block-layer-build geometry (MOLB-PPA SOFC) and a planar geometry with trapezoidal baffles inside the fuel and air channels (P-TBFA SOFC). The results for power density at different current densities are discussed. Also, a comparison of the field of species concentration, temperature, and current density on the electrode–electrolyte interface is analyzed at a defined power density. Finally, a comparison of maps of the local entropy generation rate and the global entropy generation due to heat transfer, fluid flow, mass transfer, activation loss, and ohmic loss are studied. The results show that the MOLB-PPA SOFC reaches a 7.5% higher power density than the P-TBFA SOFC. Furthermore, the P-TBFA SOFC has a more homogeneous temperature distribution than the MOLB-type SOFC. The entropy generation analysis indicates that the MOLB-PPA SOFC exhibits lower global entropy generation due to heat transfer compared to the P-TBFA SOFC. The entropy generation due to ohmic losses is predominant for both geometries. Finally, the total irreversibilities are 24.75% higher in the P-TBFA SOFC than in the MOLB-PPA SOFC.